Quercetin ameliorates Di (2-ethylhexyl) phthalate-induced nephrotoxicity by inhibiting NF-κB signaling pathway. Issue 2 (3rd March 2022) - Ashari, Sorour; Karami, Mohammad; Shokrzadeh, Mohammad; Bagheri, Abouzar; Ghandadi, Morteza; Ranaee, Mohammad; Dashti, Ayat; Mohammadi, Hamidreza
Abstract: This study aimed to evaluate the possible protective effects of quercetin, a natural flavonoid, against nephrotoxicity induced by Di (2-ethylhexyl) phthalate (DEHP) in kidney tissue of rats and human embryonic kidney (HEK) 293 cell line. The HEK-293 cells were treated with different concentrations of quercetin 24 h before treatment with monoethylhexyl phthalate (MEHP). Male rats were treated with 200-mg/kg DEHP, 200-mg/kg DEHP plus quercetin (50 and 100 mg/kg), and 200-mg/kg DEHP plus vitamin E (20 mg/kg) for 45 days by gavage. Quercetin treatment reduced cytotoxicity and oxidative damage inducing by MEHP in HEK-293 cells. The in vivo findings showed that 100-mg/kg quercetin significantly suppressed DEHP-induced kidney damage. For exploring the involved mechanisms, the expressions of nuclear factor E2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), nuclear factor kappa B (NFκB), and tumor necrosis factor alpha (TNFα) genes were determined via real-time Polymerase chain reaction (PCR) assay. High dose of quercetin significantly decreased the gene expressions of NF-κB and TNFα, whereas the alternations of Nrf2 and HO-1 gene expressions were not significant in quercetin groups in compared with DEHP group. These findings suggested that the suppression of DEHP-induced nephrotoxicity via quercetin is correlated, at least in part, with its potential to regulate NF-κB signaling pathway. Graphical Abstract: